Macquarie Island Polarisation Lidar data, 2016-2018 - ALEXANDER, SIMON (hasPrincipalInvestigator); ALEXANDER, SIMON (processor); Australian Antarctic Data Centre (publisher)
The dataset consists of the raw signal return from the AAD POLAR (Polarisation) lidar for both the co-polarisation and cross-polarisation channels. Resolution: 30m vertically x 10 seconds Time period: April 2016 - March 2018. Note that the data have not been range-corrected, overlap-corrected, calibrated nor background-corrected. These need doing prior to using these data for further analyses.